Occurrence of Nutritional Status Problems (Stunting) in Cities and Villages in Children in Kediri - Maria Yusiana; Sandy Kurniajati; Srinalesti Mahanani; Dewi Ika Sari HP (STIKes Patria Husada Blitar, 2021)
The current trend of maternal and child health problems is stunting. Health development 2015-2019 is focused on decreased in maternal and infant mortality, a decreased in the prevalence of short toddler (Stunting). The purpose of the study was compared stunting in the cities and village to children in Kediri. The research method used a comparative observation with the population of children in the City of Bangsal Kediri and Dusun Bulakdawung, Parang Kediri Village, with a sample of 49 children. Sampling using Nutritional Status based on BB/U and TB/U. Data was collected by observing spring and microtoise scales. The analysis used is Mann-Whitney. Nutritional status based on BB/U nutritional problems in the city 13.8% and in the village 5%, nutritional problems TB/U (stunting) in the city 3.4% and in the village 10%. Comparison of nutritional status based on BB/U p = 0.34 and TB/U p = 0.362 there is not significant. The main factor in nutritional problems is that the nutrients consumed are not appropriate, both in quality and quantity.The community in Parang Banyakan Village, Kediri is a mountainous community, the dominant vegetable protein rather than animal. Secondary factors of insufficient nutrition are caused by disruptions in the utilization of nutrients. In Kediri City Ward, children's malnutrition problems are not always caused by inadequate nutritional intake, child health factors such as disorders in children that cause nutrition cannot be absorbed by the body, and children experience the frequency of recurrent infections, so the child's nutrition is not for growth and development but to fight infection.